We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
321
3
avatar+866 

What real number is equal to the expression \(2 + \frac{4}{1 + \frac{4}{2 + \frac{4}{1 + \cdots}}}\), where the 1s and the 2s alternate?

 May 8, 2018
 #1
avatar+101084 
+5

Let  a   =  2  +   4

                       ______

                       1 +   4

                              ____

                                 ........

                          

 

So we have

 

a =   2  +       4

                  ____

                 1  + 4

                       __

                        a           simplify

 

 

 

a =   2      +    4a

                    _______

                      (a  + 4)

 

 

a   =  (2a + 8 + 4a) 

         _____________

             (a + 4)

 

 

a( a + 4)  =   6a + 8

 

a^2 + 4a   = 6a  + 8

 

a^2 - 2a  - 8   = 0

 

(a - 4) (a + 2)    = 0

 

Setting both factors to 0  and solving for   "a"  we  get   that  a  = 4  or a  = -2

 

We can reject -2 because  a  is positive

 

So......the real  number is   4

 

 

 

cool cool cool               

 May 8, 2018
 #2
avatar+866 
+2

Thank you, CPhill! laugh

ant101  May 8, 2018
 #3
avatar+4247 
+3

Solution:

So, we have \(2+\frac{4}{1+\frac{4}{2+\frac{4}{1+\cdots}}} \), which at first looks rather scary. But we notice a pattern! Because the nested fractions descend forever, the fraction essentially contains itself! So let \(a\)  equal this fraction:

\( a = 2+\frac{4}{1+\frac{4}{2+\frac{4}{1+\cdots}}} \)

Thus,

\( a = 2+\frac{4}{1+\frac{4}{a}} \)

So now, we simply need to solve for a.

\(a = 2+\frac{4}{1+\frac{4}{a}} = 2 + \frac{4}{\frac{4+a}{a}}= 2+\frac{4a}{4+a}=\frac{8+2a+4a}{4+a}=\frac{8+6a}{4+a}\)


Getting rid of the fraction by multiplying y \(4+a\), we get

\(4a + a^2 = 8 + 6a \Longrightarrow a^2 - 2a - 8 = 0\)



So now we factor...

\(a^2 - 4a + 2a - 8 = 0\)

\(a(a-4)+2(a-4) = 0\)

\((a+2)(a-4) = 0\)  





So \(a\) can be \(-2\) or \(4\). Since we know, by looking at the fraction, that \(a\)  must be positive, \(a\), and the value of the fraction, must be \(\boxed{4}\).

 

Tell me if you have any questions,

smileysmiley

 May 8, 2018

6 Online Users

avatar